2001
DOI: 10.1080/10715760100300431
|View full text |Cite
|
Sign up to set email alerts
|

Selective distribution of oxysterols in atherosclerotic lesions and human plasma lipoproteins

Abstract: The presence of oxidized sterols (oxysterols) in human serum and lesions has been linked to the initiation and progression of atherosclerosis. Data concerning the origin, identity and quantity of oxysterols in biological samples are controversial and inconsistent. This inconsistency may arise from different analytical methods or handling conditions used by different investigators. In the present study, oxysterol levels and distribution were analyzed by an optimized GC-MS method, in human atherosclerotic corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 44 publications
2
68
0
4
Order By: Relevance
“…Furthermore, we found a striking correlation between an increase in endothelial stiffness and the amount of oxysterols in oxLDL. These observations are consistent with strongly oxidized LDL having more impact on endothelial stiffness compared with mmLDL, because although In terms of the presence of oxysterols in vivo, earlier studies have shown that oxysterols are found in vascular tissues of ApoE Ϫ / Ϫ mice with advanced atherosclerosis, as well as in human atherosclerotic lesions ( 25,65 ). Our studies show that a signifi cant accumulation of oxysterols was found in aortic tissue of male ApoE Ϫ / Ϫ mice fed a low-cholesterol chow diet at a very early stage of disease progression (10-12 weeks of age) when typically no foam cell lesions are observed ( 52 ).…”
Section: Incorporation Of Oxysterols Into Endothelial Membranessupporting
confidence: 75%
“…Furthermore, we found a striking correlation between an increase in endothelial stiffness and the amount of oxysterols in oxLDL. These observations are consistent with strongly oxidized LDL having more impact on endothelial stiffness compared with mmLDL, because although In terms of the presence of oxysterols in vivo, earlier studies have shown that oxysterols are found in vascular tissues of ApoE Ϫ / Ϫ mice with advanced atherosclerosis, as well as in human atherosclerotic lesions ( 25,65 ). Our studies show that a signifi cant accumulation of oxysterols was found in aortic tissue of male ApoE Ϫ / Ϫ mice fed a low-cholesterol chow diet at a very early stage of disease progression (10-12 weeks of age) when typically no foam cell lesions are observed ( 52 ).…”
Section: Incorporation Of Oxysterols Into Endothelial Membranessupporting
confidence: 75%
“…Given these results in animal models, it is likely that oxidized cholesterol in the diet would also accelerate atherosclerosis in humans. In fact, oxidized cholesterol is found in human foam cells and advanced atherosclerotic lesions (30,31). In individuals with atherosclerosis, plasma levels of oxidized cholesterol appear to be higher than in healthy controls (50), and coronary atherosclerosis is reflected by autoantibodies against oxidized LDL and oxidized cholesterol in the serum (51).…”
Section: Discussionmentioning
confidence: 99%
“…It was purchased from Steraloids Inc. (Newport, RI), and was selected because it is one of the major oxidized cholesterol components in heated or stored foods (10)(11)(12)(13). It has also been detected in human serum (27)(28)(29) and atherosclerotic lesions (30,31). It is efficiently absorbed as indicated by studies with experimental animals (19).…”
Section: Experimental Diets and Study Protocolmentioning
confidence: 99%
“…There are considerable data demonstrating that lipoproteins are oxidized locally in the intima of the arterial wall (1-4) as well as evidence that oxidized lipoproteins are present in human serum (5,6). These circulating oxidized lipoproteins can be taken up by the arterial wall and thereby contribute to the levels of oxidized lipoproteins in the intima.…”
Section: Supplementary Abstract Oxidized Lipoproteinsmentioning
confidence: 99%